Reconstructive techniques in skull base surgery after resection of malignant lesions: a wide array of choices. Issue 2 (April 2016) - Hachem, Ralph Abi; Elkhatib, Ahmad; Beer-Furlan, Andre; Prevedello, Daniel; Carrau, Ricardo
Abstract : Purpose of review: In this manuscript, we will provide a panorama of the current status of skull base reconstruction following endoscopic endonasal or open resection of malignant lesions, focusing on novel options and recent modifications of previously described techniques. Recent findings: New developments in skull base reconstruction continue to arise, mostly as in the form of vascularized pedicled flaps that can be used following endoscopic and open resections of the skull base. Summary: Resection of skull base tumors, often creating large dural defects that couple with extensive intradural dissection, involving multiple cisterns or the third ventricle, may lead to high-flow cerebrospinal fluid leaks. Reconstruction of the skull base is paramount to achieve an uncomplicated postoperative course. Repair of small dural defects can be reliably achieved using a multilayer grafting technique, which yields a high success rate (>90%). Repair of larger defects associated with a high-flow cerebrospinal fluid leak, or defects in previously irradiated fields, often requires a local or regional pedicled vascularized graft as the first reconstructive choice. When these are unavailable, free microvascular tissue transfer remains an option.